SPONTANEOUS REMISSION OF GRAVES’ DISEASE FOLLOWING SYSTEMIC LUPUS ERYTHEMATOSUS TREATMENT: A CASE REPORT - Lau, Simran; Zhi, Lim Hui; Ng, Ooi Chuan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Hyperthyroidism secondary to Graves’ disease is typically managed with thionamides, radioiodine therapy, or thyroidectomy. However, spontaneous remission is uncommon, especially after prolonged thionamide therapy. This case highlights a rare instance of hyperthyroidism remission one year after treatment with steroids for systemic lupus erythematosus (SLE), despite seven years of prior thionamide use. CASE A 25-year-old Malay female with type 1 diabetes mellitus (T1DM) and SLE was diagnosed with Graves’ disease at age 15 and treated with carbimazole for seven years. Hyperthyroidism resolved three years before her SLE diagnosis. In 2021, she was diagnosed with Class IV/V lupus nephritis and started on high-dose corticosteroids (methylprednisolone and prednisolone) with cyclophosphamide. One year after initiating steroid therapy, thyroid function tests (TFTs) remained euthyroid without antithyroid medication. Repeat TFTs confirmed continued remission. Several mechanisms may explain the remission of Graves’ disease in this case. High-dose corticosteroids suppress autoreactive B and T lymphocytes, potentially reducing thyrotropin receptor antibody (TRAb) production and facilitating remission. Additionally, corticosteroids enhance regulatory T-cell (Treg) activity, restoring immune tolerance and reducing autoimmunity. The presence of multiple autoimmune diseases suggests a broader dysregulation of immune function, thus immunosuppressive therapy for SLE may have inadvertently suppressed the pathogenic mechanisms driving Graves’ disease. Lastly, long-standing autoimmunity can lead to immune exhaustion, where autoreactive immune cells become less active over time, potentially contributing to spontaneous remission. CONCLUSION Although corticosteroids are not a conventional treatment for hyperthyroidism, their immunomodulatory effects may inadvertently promote disease remission in select cases. This highlights the need for further research to elucidate the potential role of immunosuppressive therapy in achieving sustained remission of autoimmune hyperthyroidism.